Current-Mode First-Order Versatile Filter Using Translinear Current Conveyors with Controlled Current Gain - Montree Kumngern; Wirote Jongchanachavawat; Punnavich Phatsornsiri; Natapong Wongprommoon; Fabian Khateb; Tomasz Kulej (My University, 2023)
This paper offers a new current-mode first-order versatile filter employing two translinear current conveyors with controlled current gain and one grounded capacitor. The proposed filter offers the following features: realization of first-order transfer functions of low-pass, high-pass, and all-pass current responses from single topology, availability of non-inverting and inverting transfer functions for all current responses, electronic control of current gain for all current responses, no requirement of component-matching conditions for realizing all current responses, low-input impedance and high-output impedance which are required for current-mode circuits, and electronic control of the pole frequency for all current responses. The proposed first-order versatile filter is used to realize a quadrature sinusoidal oscillator to confirm the advantage of the new topology. To confirm the functionality and workability of new circuits, the proposed circuit and its application are simulated by the SPICE program using transistor model process parameters NR100N (NPN) and PR100N (PNP) of bipolar arrays ALA400-CBIC-R from AT&T.
Keywords: Output impedance; Current conveyor; Electronic filter topology; Electronic component; Analog and Mixed-Signal Circuit Design